A Thousand Barrels a Second: The Coming Oil Break Point and the Challenges Facing an Energy Dependent World - Tertzakian Peter (Mc Graw Hill, 2007)
A Powerful Analysis of Our Oil Addiction and a New Direction for Global Energy